Understanding how socioecological factors affect COVID-19 vaccine perceptions among adolescents: qualitative evidence from seven high-, middle- and low-income countries - Astha Ramaiya; Kristin Mmari; Ana Luiza Borges; Christiane Cabral; Eric Mafuta; Aimee Lulebo; Chunyan Yu; Anggriyani Wahyu Pinandari; Siswanto Agus Wilopo; Effie Chipeta; Kara Hunersen (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background The number of studies examining family, community, institutional and policy factors on COVID-19 vaccine perceptions is limited, with most concentrating on high-income countries and using predominantly quantitative methods. To address this gap, the goal of this manuscript is to qualitatively explore these factors and how they shape adolescents' perspectives on COVID-19 vaccines across diverse contexts. # Methods Focus group discussions were conducted among adolescent populations (13 - 18 years) across seven countries: Ghent, Belgium; Sao Paulo, Brazil, Shanghai; China, Kinshasa, Democratic Republic of Congo (DRC); Semarang and Denpasar, Indonesia; Blantyre, Malawi and New Orleans, United States of America (USA). An inductive thematic analytical approach was used to understand the emerging themes across the different countries based on the study's objectives. # Results The study found that all influences were inter-connected and contributed towards vaccine perceptions among adolescents, which were largely positive except in the two African countries and to an extent in the USA. Family and community influences played a large role in vaccine perceptions, however, this differed by context. Our findings suggest adolescents' perceptions about vaccines were more positive in countries with higher vaccination rates, i.e. China and Indonesia versus countries with lower vaccination rates i.e. Malawi and DRC. Vaccine mandates within schools, offices, and public places were also discussed with varying perceptions based on government trust. # Conclusions Adolescents' perceptions of the Covid-19 vaccine are based on a variety of elements, such as families, community, institutions, and policies. Prioritizing one or another path may not be sufficient to improve vaccine adherence during future pandemics, as we experienced with Covid-19. Strategies to make vaccine perceptions more positive among urban poor adolescents should address both family and community perceptions. However, policies and robust programs around immunization are still needed.